2005
DOI: 10.1038/sj.mp.4001656
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived neurotrophic factor Val66met polymorphism and volume of the hippocampal formation

Abstract: Magnetic resonance (MR) imaging studies have identified hippocampal structural alterations in the pathogenesis of schizophrenia. Brain-derived neurotrophic factor (BDNF) is one of the neurotrophins that is widely expressed in the hippocampal formation and has been implicated in the neurobiology of schizophrenia. Polymorphisms in the BDNF gene may therefore confer risk for schizophrenia through hippocampal pathogenesis and/or making the hippocampus more susceptible to environmental insults. In this study, we in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
240
6
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 343 publications
(271 citation statements)
references
References 46 publications
20
240
6
5
Order By: Relevance
“…This is in contrast with the literature where the BDNF val66met-allele Hariri et al, 2003;Pezawas et al, 2004;Szeszko et al, 2005;Bueller et al, 2006) Memory performance in the CYP46 genotypes is listed in Table 1. We correlated memory performance with the parahippocampal and hippocampal GM volumes derived from the VOIs (Table 3).…”
Section: Resultscontrasting
confidence: 88%
See 3 more Smart Citations
“…This is in contrast with the literature where the BDNF val66met-allele Hariri et al, 2003;Pezawas et al, 2004;Szeszko et al, 2005;Bueller et al, 2006) Memory performance in the CYP46 genotypes is listed in Table 1. We correlated memory performance with the parahippocampal and hippocampal GM volumes derived from the VOIs (Table 3).…”
Section: Resultscontrasting
confidence: 88%
“…The MRI T1-weighted intensity profiles, on which morphometric MRI studies are based, have been shown to be best explained by a weighted sum of cytoarchitectonic and myeloarchitectonic profiles (Eickhoff et al, 2005), suggesting that the volumetric differences originate in differences in neuronal and synaptic compartments, which are very important for brain functions, rather than differences in the stroma (including interstitial fluid) or edema. Although several morphometric imaging studies found support for an association of the BDNF val66met SNP (rs6265) with volumetric differences in MTL structures and memory performance Hariri et al, 2003;Pezawas et al, 2004;Szeszko et al, 2005;Bueller et al, 2006), we were unable to replicate the finding of smaller hippocampal volumes in BDNF val66met carriers compared with val66val carriers within our dataset. Possible explanations include the diversity of methodological approaches applied to measure the volume of interest, the restricted age range of our subjects, the high level of education of our academic sample, the fact that we controlled for genetic variation in additional SNPs as well as background genetic heterogeneity, and/or the different numbers of BDNF met66met carriers…”
contrasting
confidence: 76%
See 2 more Smart Citations
“…Although here we did not examine specific candidate genes that may contribute to the observed hippocampal alterations, brain-derived neurotrophic factor (BDNF) is widely expressed in the hippocampus and has been implicated in the neurobiology of schizophrenia. Szeszko et al [2005] found differences in hippocampal volume as a function of BDNF (val66met) genotype in a combined sample of schizophrenia patients and controls and, secondly, that genotype explained more variance in hippocampal volume for schizophrenia patients relative to healthy volunteers. This suggests that the BDNF gene may contribute to variation in human hippocampal volume, and that this effect may be amplified in patients with schizophrenia.…”
Section: Heritability Of Brain Structure In Twins Discordant For Schimentioning
confidence: 77%